Imagining home: literary fantasy in contemporary Chinese diasporic women’s literature - Tang, Fang (2018)
This thesis explores the use of literary fantasy in the construction of identity and ‘home’ in contemporary diasporic Chinese women’s literature. I argues that the use of fantasy acts as a way of undermining the power of patriarchal values and unsettling fixed notions of home. In each of these four texts by Chinese diasporic women author, the authors or their protagonists describe different explorations of the search for home: a space where they can articulate their voices and desires. The notion of home for these diasporic Chinese women is much more complex than a simple feeling of nostalgia in response to a state of displacement and unhomeliness. The idea of home relates to complicated struggles to gain a sense of belonging, as experienced by marginalized subjects constructing their diasporic identities — which can best be understood as unstable, shifting, and shaped by historical conditions and power relations.